Design and numerical analysis of an efficient H-Darrieus vertical-axis hydrokinetic turbine (2019)
Hydrokinetic turbines are one of the technological alternatives to generate and supply electricity for rural communities isolated from the national electrical grid with almost zero emission. The Darrieus turbine is one of the options that can be used as a hydrokinetic turbine due to its high power coefficient (Cp) and easy manufacture. In the present work, the design and hydrodynamic analysis of a Darrieus vertical-axis hydrokinetic turbine of 500 W was carried out. A free stream velocity of 1.5 m/s was used for the design of the blades. The diameter (D) and blade length (H) of the turbine were 1.5 m and 1.13 m, respectively. The blade profile used was NACA0025 with a chord length of 0.33 m and solidity () of 0.66. Two (2D) and three dimensional (3D) numerical analyses of the unsteady flow through the blades of the turbine were performed using ANSYS Fluent version 18.0, which is based on a Reynolds-Averaged Navier-Stokes (RANS) model. A transient 2D simulation was conducted for several tip speed ratios (TSR) using a k-ω Shear Stress Transport turbulence (SST) scheme. The optimal TSR was found to be around 1.75. Main hydrodynamic parameters, such as torque (T) and CP, were investigated. Additionally, 3 geometrical configurations of the turbine rotor were studied using a 3D numerical model in order to identify the best configuration with less Cp and T fluctuation. The maximum Cp average was 0.24 and the amplitude of Cp variation, near 0.24 for the turbine model with 3 blades of H equal to 1.13 m. On the other hand, for the turbine models with 6 and 9 blades of H equal to 0.565 m and 0.377 m, respectively, the maximum Cp averages were 0.51 and 0.55, respectively, and the amplitude of Cp variation, near 0.07 for the model with 6 blades and 0.17 for the model with 9 blades. This revealed that the hydrokinetic turbine with a geometrical configuration of 6 blades greatly improves the performance of the turbine due to this model has advantages compared to models with 3 and 9 blades, in terms of the reduction of their T curve fluctuation. Keywords: Darrieus hydrokinetic turbine; numerical simulation; power coefficient; tip speed ratio.